Islamic Education and Moral Formation: A Study on Junior High School Students - Fatulloh Fatulloh; Siswo Teguh Pranoto (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: to prove the influence of Islamic Religious Education learning on students' morals at Satria Nusantara Junior High School, North Tambun, Bekasi. Methodology: This study uses a survey method with correlational analysis techniques. The sample of this study was 45 eighth grade students of Satria Nusantara Junior High School, North Tambun, Bekasi Regency. Data collection used a questionnaire instrument to capture data on variables X and Y. The research variables consist of the independent variable, namely Islamic Religious Education learning, and the dependent variable, namely the morals of students of Satria Nusantara Junior High School, North Tambun, Bekasi Regency. The validity of the instrument was tested using the Product Moment formula and to determine its reliability, it was tested using the Cronbach Alpha formula. The data analysis technique used the Product Moment test and simple linear regression test, which had previously been tested for normality and homogeneity. Main Findings: there is an influence of Islamic Religious Education learning on students' morals which can be seen based on the calculated r value = 0.780 with a strong interpretation with a contribution of 60.8%, and a significance of t count = 8.168 > t table = 2.021. The regression equation Y = 48.28 + 0.65X shows that if Islamic Religious Education learning and students' morals are measured by the instrument used in this study, then every increase in one unit of Islamic Religious Education learning score (X) will be followed by a decrease in students' moral scores by 0.65 with a constant of 48.28. Novelty/Originality of this study: This study offers originality by empirically examining the impact of Islamic Education on students’ moral development in the context of a junior high school in Indonesia, a setting rarely highlighted in global discourse. Unlike previous research that emphasizes curriculum or pedagogy, this study quantitatively demonstrates the direct influence of Islamic Education on students’ character, contributing evidence-based insights to moral and religious education studies.